Editorial - Braude, Stephen (Journal of Scientific Exploration, 2014)
This issue of the JSE is appearing rather later than originally planned, and not because (or at least not simply because) I and my editorial team members are slackers who prefer debauchery to diligent work on the Journal. The Spring JSE issue was supposed to be an issue focusing on physical mediumship generally and the case of the Felix Experimental Group (FEG) in particular. Some readers might recall that I've given two SSE presentations on my experiences with that German group, including my report, last June, on some intriguing and carefully controlled-but still inconclusive-séances at a secure private farmhouse in Austria belonging to one of the investigators. Those Austrian sessions yielded videos of a table apparently levitating in red light and the medium pulling large quantities of ectoplasm from his mouth, which then accumulated in an apparently animated heap on the floor in front of him. The ectoplasm was produced despite numerous controls, including a careful strip search of the medium, examination of the medium's clothes, and inspection of the cabinet in which he sat. As the Spring issue approached the proofreading stage, with two long reports on the FEG ready to go, various pieces of evidence surfaced casting serious doubt on some (though not all) of the FEG phenomena. The case, constructed by one of my co-investigators, is so far largely circumstantial, but it's by no means trivial. And so it quickly became clear that the papers scheduled for the Spring issue needed to be massively rewritten, and the FEG phenomena generally carefully re-assessed in light of the recent developments. As a result, the physical mediumship issue is now planned for the summer. Of course, this last-minute decision required us to move some other already-accepted papers to this issue and then (naturally) to engage in very late and time-consuming flurries of copyediting and proofreading. So I apologize for the delay in preparing this issue for distribution, but when the mediumship issue finally appears over the summer, the reports on the FEG will be more nuanced and authoritative, and probably more complex, than they were before. In the meantime, you now have before you a very substantive collection of papers on a healthy variety of topics, illustrating nicely the vital diversity of issues pursued by SSE members and addressed within the pages of the JSE. Our lead research paper reports a study in which inexperienced remote viewers attempted to use associative remote viewing to predict the Dow Jones Industrial Average. That's followed by a paper on the biological anomalies reported in the 1999 Hoeven crop circle and a recent effort to replicate the anomalies normally. The next paper challenges the prevailing view of how and when the Americas were settled by re-evaluating and defending the possibility of pre-Columbian transoceanic travels. These papers are followed by a characteristically well-researched historical perspective paper by Carlos Alvarado, another provocative essay by my editorial predecessor Henry Bauer, and our usual varied array of interesting book reviews. Stephen E. Braude